Conservation sensitivity: A Case of Lubhu - Thapa, Shova; Sebi Nakarmi; Aaradhana Shrestha; Aditi Chhetri; Garima Neupane; Sushmita Gautam (Journal of Innovations in Engineering Education, 2024)
Lubhu which is a 700-year-old traditional Newari settlement just 6 km east of Patan Lalitpur, Nepal. Being so close to Patan and having similarities in culture and traditions, Lubhu has much more to offer strong historical and cultural significance of the Newari settlement in Kathmandu Valley. However, the town has been developing rapidly risking the extinction of historical and cultural practices and uniqueness of the city. This research intends to find the conservation sensitivity of the local people living in Lubhu. The study concentrates on the Jatra Route and assesses the awareness, attitude, and involvement of the locals toward the conservation of traditional elements, rituals, and heritage sites. The methodology involves qualitative methods such as semi-structured interviews with the stakeholders, locals, and heritage experts and the quantitative method includes a questionnaire and survey. The finding reveals that the majority of the people support the conservation of traditional elements such as monuments, temples, and traditional infrastructures. This study also shows that the people of Lubhu strongly believe that the government is responsible for the conservation of this ancient town rather than another organization or local people, while also revealing prevalent bias among locals regarding the relationship between development and conservation. The study concludes that some people perceive these two goals conflictingly, believing that efforts to preserve cultural heritage hinder progress and modernization.